5α-Reductase: History and Clinical Importance - Marks, Leonard S (MedReviews, LLC, 2004)
The treatment of men with symptomatic benign prostatic hyperplasia (BPH) has shifted dramatically from surgery to drug therapy over the past decade. The revolution in BPH treatment began with the discovery of congenital 5α-reductase (5AR) deficiency, leading to the appreciation of 2 different androgenic hormones: testosterone, which mediates overt masculinization in the adult male, and dihydrotestosterone (DHT), which mediates prostatic growth, acne, facial beard, and male pattern baldness. Inhibition of DHT in adults results in prostatic shrinkage and symptomatic relief in many men, without the side effects seen with conventional androgen-deprivation therapy. The 5AR inhibitor drugs (finasteride and the dual inhibitor, dutasteride) are able to ablate the accumulation of intraprostatic DHT, the mechanism most responsible for prostate growth and maintenance. Not only may these drugs relieve symptoms, but they may also alter the natural history of the BPH process. Future indications for the 5ARI drugs could include chemoprevention of prostate cancer, prophylaxis of BPH-related complications, and treatment of BPH-associated hematuria.